Secondary Rhinoplasty: Management of the Overresected Dorsum - Daniel, Rollin K.; Sajadian, Ali (Facial Plastic Surgery, 2012)
Any discussion of grafting the dorsum in secondary rhinoplasty must take into account the different indications (aesthetic, augmentation, and structure) as well as recent changes in materials and techniques (fascia, diced cartilage). We have placed solid dorsal grafts with diced cartilage grafts either as an isolated diced cartilage graft in fascia graft or as the aesthetic dorsal contour layer of a composite reconstruction. The rational for this profound change in selection and indication of dorsal grafts for revising the overresected dorsum will become clear as the various alternative materials and techniques are analyzed. Currently, we only employ autogenous tissues.
Keywords: revision rhinoplasty; grafts; implants; diced cartilage grafts